Enhancement Learning Results Fiqih Study Materials Through Method Discussion on Participant Educate Class VIII F Mts. Manbail Futuh Beji Jenu Tuban - Fikriyah, Eniq; Said, Nur; Muniron; Sufirmasnyah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The background to this research is: 1) The low ability of students to understand the subject matter. 2) Student activity is still dominated by only smart students. 3) Lack of student competency results after studying halal food and haram food material. The aim of this research: to improve learning outcomes in fiqh subject matter for students in class VIII F MTs. Manbail Futuh Beji Jenu Tuban Academic Year 2023/2024 through the discussion method. The method used in this research is the discussion method. The research results show an increase in student learning outcomes. Where in the first cycle, 13 students (72%) achieved the KKM, less than the specified 90%. In cycle II, students who achieved the KKM increased to 17 people (94%), more than the 90% set. So it can be concluded that using the discussion method can improve FIQIH learning outcomes for class VIII MTs students. Manbail Futuh Beji Jenu Tuban Academic Year 2023/2024 Write abstract in English, use Times New Roman 10 for body of the abstract with one spacing between lines, justified, consists of a maximum 150 words. Inform; the issue, purpose (contains objectives of the research), method (delivers data collection of the research), results of the research (refers to collected data as an effort to answer research question), impact and conclusion (summary of the finding and the result of the research).